The utility of ultrasound and computed tomography in the assessment of carotid artery plaque vulnerability–A mini review - Singh, Aniruddha; Nasir, Usama; Segal, Jared; Waheed, Tayyab Ali; Ameen, Muhammad; Hafeez, Hamza (Frontiers in Cardiovascular Medicine, 2022)
As the burden of cardiovascular and cerebrovascular events continue to increase, emerging evidence supports the concept of plaque vulnerability as a stronger marker of plaque rupture and embolization. Qualitative assessment of the plaque can quantify the degree of plaque instability. Ultrasound and Computed tomography (CT) have emerged as safe and accurate techniques for the assessment of plaque vulnerability. Plaque features including but not limited to surface ulceration, large lipid core, thin fibrous cap, intraplaque neovascularization and hemorrhage can be assessed and contribute to plaque vulnerability and rupture